Job satisfaction among licensed librarian along Herzberg's Hygiene-Motivation theory in the Philippine setting - Wee, Ma Mercedes L.; Santos, Herminia H.; Sison, Josephine C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2000)
The study focused on job satisfaction of licensed librarians. It sought to answer the following questions: What determines the level of satisfaction of licensed librarians along Herzberg's-Motivation Theory What are the educational programs and alternative means to enhance the job satisfaction of these librarians Is Herzberg's Hygiene-Motivation Theory applicable to librarians professional Data were collected by means of questionnaires and interviews. The sample included 204 licensed librarians from the different types of libraries namely: special, public, school and academic and research libraries.
The t-test was used to test the hypothesis that librarians have an undecided average response to the Hygiene-Motivation Factors. The hypothesis was proved to be significant since the Ho was rejected at a0.05. On the basis of the sample, there is enough evidence to conclude that the mean score of the librarians differ significantly on the average from 3, which means the librarians are satisfied with their jobs. Since we reject the null hypothesis (Ho), we conclude with 95 percent confidence that the average response of librarians for hygiene-motivation factors are "very satisfied" and that they are happy with their work. The results show that the Herzberg's Hygience-Motivation Theory is validated among librarians.
Computer print out.
Vita.
Special Problem (Master of Library Science)
Keywords: Librarians -- Job satisfaction -- Philippines; Motivation (Psychology) -- Philippines